La Omisión de los Grados de Afinidad en la Ley de Donación de Órganos en el Ecuador - Salinas Pauta, Giovanna Alexandra (2016)
This thesis is focused on the study of existing problems as regards living donation, since in the organic law of donation and transplantation of organs, tissues and cells, specifically article 33 paragraph b, points out the limitation to donate can do so up to the fourth degree of consanguinity, all this constitutes a failure to degrees of affinity and a limiting factor for people who suffer from catastrophic illnesses, considering that among which are those who they need a transplant, those suffering from chronic renal failure. For all this, this research work has as its main axis, a study because transplants are necessary and as are a humanitarian issue and solidarity to prolong the life of a person, plus as organ transplantation is carried out in Ecuador , development and evolution, and limitations were given and how they can be overcome. In addition, it is taking into account the historical background of both the donation and transplantation and how it has allowed to have a broader and futuristic vision on this issue, as the laws of Mexico and Panama, take into greater consideration, compatibility between donor and recipient, before blood kin, and this is where there is a glimmer of light for this big question, is it necessary to be familiar to donate ?, research shows clearly both the theoretical content, such as interviews with professionals health, the key is in the blood compatibility, and that much more immunosuppressive drugs, which will allow the recipient does not reject the organ. It brings to discussion important issues such as: organ trafficking, and as this constituted at the time of issuance of the law above, a defense mechanism to forewarn and legally ensure people, but both the laws and the peoples they govern evolve, they must be subject to change, for the betterment of life and access to health they themselves proclaim, therefore its adjustment to current needs is necessary, as our criminal comprehensive organic code it is the legal support, which our society rests, in which typifies and organ trafficking.